Targeting Pin1 by All-Trans Retinoic Acid (ATRA) Overcomes Tamoxifen Resistance in Breast Cancer via Multifactorial Mechanisms - Huang, Songyin; Chen, Yang; Liang, Zhi-Mei; Li, Na-Na; Liu, Yujie; Zhu, Yinghua; Liao, Dingzhun; Zhou, Xiao Zhen; Lu, Kun Ping; Yao, Yandan; Luo, Man-Li (Frontiers in Cell and Developmental Biology, 2019)
Breast cancer is the most prevalent tumor in women worldwide and about 70% patients are estrogen receptor positive. In these cancer patients, resistance to the anticancer estrogen receptor antagonist tamoxifen emerges to be a major clinical obstacle. Peptidyl-prolyl isomerase Pin1 is prominently overexpressed in breast cancer and involves in tamoxifen-resistance. Here, we explore the mechanism and effect of targeting Pin1 using its chemical inhibitor all-trans retinoic acid (ATRA) in the treatment of tamoxifen-resistant breast cancer. We found that Pin1 was up-regulated in tamoxifen-resistant human breast cancer cell lines and tumor tissues from relapsed patients. Pin1 overexpression increased the phosphorylation of ERα on S118 and stabilized ERα protein. ATRA treatment, resembling the effect of Pin1 knockdown, promoted ERα degradation in tamoxifen-resistant cells. Moreover, ATRA or Pin1 knockdown decreased the activation of ERK1/2 and AKT pathways. ATRA also reduced the nuclear expression and transcriptional activity of ERα. Importantly, ATRA inhibited cell viability and proliferation of tamoxifen-resistant human breast cancer cells in vitro. Slow-releasing ATRA tablets reduced the growth of tamoxifen-resistant human breast cancer xenografts in vivo. In conclusion, ATRA-induced Pin1 ablation inhibits tamoxifen-resistant breast cancer growth by suppressing multifactorial mechanisms of tamoxifen resistance simultaneously, which demonstrates an attractive strategy for treating aggressive and endocrine-resistant tumors.